Diagnostic accuracy of a global cognitive screen for Māori and non‐Māori octogenarians. Issue 1 (1st January 2019) - Zawaly, Kristina; Moyes, Simon A.; Wood, Phil C.; Cheung, Gary; Rolleston, Anna; Buetow, Stephen; Tippett, Lynette; Kerse, Ngaire
Abstract: Introduction: We assessed the sensitivity and specificity of the Modified Mini–Mental State Examination (3MS) in predicting dementia and cognitive impairment in Māori (indigenous people of New Zealand) and non‐Māori octogenarians. Methods: A subsample of participants from Life and Living in Advanced Age: a Cohort Study in New Zealand were recruited to determine the 3MS diagnostic accuracy compared with the reference standard. Results: Seventy‐three participants (44% Māori) completed the 3MS and reference standard assessments. The 3MS demonstrated strong diagnostic accuracy to detect dementia with areas under the curve of 0.87 for Māori and 0.9 for non‐Māori. Our cutoffs displayed ethnic variability and are approximately 5 points greater than those commonly applied. Cognitive impairment yielded low accuracy, and discriminatory power was not established. Discussion: Cutoffs that are not age or ethnically appropriate may compromise the accuracy of cognitive screens. Consequently, older age and indigeneity increase the risk of mislabeled cognitive status. Highlights: The cutoffs between Māori and non‐Māori octogenarians differed. Dementia versus no dementia had good discriminant validity. Applying the typical cutoff would likely lead to misclassification of cognitive function.